Geographical Trends in Prevalence of Stomach Cancer in Nepal - Sapkota, Ganga; Mallik, Dipendra Kumar; Wagle, Bhawna; Dhakal, Sunil; Bhandari, Sapana (Nepalese Journal of Cancer, 2022)
Background: Carcinoma stomach is a multifactorial disease accounting for second most common cancer among male and fifth most common cancer among Nepalese population. The prevalence of stomach cancer is partially influenced by geographical variation, social and cultural factors that significantly affect disease reporting and seeking medical care. In this study we have analyzed geographical trends in prevalence of stomach cancer among patients visiting BPKMCH. Materials and Methods: A single center descriptive retrospective study to analyze the geographical trends among stomach cancer patients visiting BPKMCH from January 2013 to December 2017 was designed and patients’ information available at medical record were obtained. Analysis was completed with SPSS Statistics. Results: During the period of 5-year total 832 cases of stomach cancer were seen at the Department of Surgical Oncology at BPKMCH. These cases comprised of 349 female and 483 males with male to female (M: F) ratio of 1.4:1. The mean age of presentation was 55 years. Maximum number of cases 57.3% (477) were from terai region of Nepal. Conclusions: This study provides clue regarding higher cases of stomach cancer among male patients and from terai region of Nepal.